THE ROLE OF DIVIDEND POLICY AND PROFITABILITY IN SHAPING CORPORATE DEBT POLICY IN THE BANKING SECTOR IN INDONESIA - Yolanda; Murtianingsih (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to examine the effect of dividend policy and profitability on debt policy in banking companies listed on the Indonesia Stock Exchange during 2020-2022. This type of research is quantitative research, the population in this study is all banking companies listed on the Indonesia Stock Exchange during 2020-2022 and selected using purposive sampling techniques, so that a sample of 12 companies that meet the criteria is obtained. The data analysis technique used in this study is multiple regression analysis method. This research found that dividend policy has an influence on debt policy and profitability has no influence on debt policy.